The role of first‐trimester ultrasound screening for women with positive noninvasive prenatal testing results. Issue 2 (16th December 2021) - Saito, Mizue; Tokunaka, Mayumi; Goto, Minako; Takita, Hiroko; Arakaki, Tatsuya; Miyagami, Keiko; Hamada, Shoko; Oba, Tomohiro; Matsuoka, Ryu; Sekizawa, Akihiko
Abstract: Aim: This study aimed to assess the utility of ultrasound screening for pregnancies with positive noninvasive prenatal testing results for trisomy 21, trisomy 18, and trisomy 13. Methods: We performed a retrospective analysis of positive noninvasive prenatal testing results and first‐trimester ultrasound screening at our department between 2013 and 2019. Invasive genetic testing was performed if the patient had positive noninvasive prenatal testing results. Fetal ultrasound and cytogenetic data were collected. Noninvasive prenatal testing was performed in the women for advanced maternal age, nuchal translucency thickness, or history of abnormality in the previous child or relative. Results: Forty‐one pregnant women had positive noninvasive prenatal testing results for trisomy 21, trisomy 18, and trisomy 13. Twenty‐three women had positive results for trisomy 21, 13 had positive results for trisomy 18, and 5 had positive results for trisomy 13 at 11 to 14 weeks of gestation. The positive predictive value of noninvasive prenatal testing was 100% for trisomy 21, 84.6% for trisomy 18, and 100% for trisomy 13. The positive predictive value of positive noninvasive prenatal testing results and fetal morphological abnormalities was 100% for trisomy 21, trisomy 18, and trisomy 13. Conclusion: Combining an ultrasound examination with noninvasive prenatal testing resulted in a higher positive predictive value for trisomy 18. Normal ultrasound examination results can help alleviate stress caused by false‐positive noninvasive prenatal testing results. In contrast, the positive predictive value and negative predictive value for trisomy 21 were not altered by adding an ultrasound examination to noninvasive prenatal testing.